2019
DOI: 10.12991/jrp.2019.170
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol treatment reduces apoptosis and morphological alterations in cisplatin induced testis damage

Abstract: Cisplatin commonly used as a chemotheropotic agent however, it is associated with numerous side effects such as reproductive cytotoxicity. It causes spermatogenic cell death and DNA damage in spermatozoa via the formation of reactive oxygene species. Resveratrol (3,5,4'-trans-trihydroxystilbene), a natural phytoalexin, is a potent antioxidant agent, present in a wide variety of dietary sources including grapes, plums and peanuts. The aim of present study to evaluate the beneficial effects of resveratrol on cis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…Collodel et al 28 reported that RES showed an ameliorative effect against LPO and protected sperm from ROS attacks in sperm culture media mainly in mechanical techniques, such as semen cryopreservation, in which oxidative stress is exacerbated. Moreover, RES enhanced fertility and protected spermatogenesis by reducing oxidative stress and exerting anti‐apoptotic effects against testicular injury induced by many anticancer drugs 70–73 . In addition, it successfully increases the activity of the antioxidant defense system, prevents LPO, and improves the pathological changes in rats after malathion treatment 74 .…”
Section: Discussionmentioning
confidence: 99%
“…Collodel et al 28 reported that RES showed an ameliorative effect against LPO and protected sperm from ROS attacks in sperm culture media mainly in mechanical techniques, such as semen cryopreservation, in which oxidative stress is exacerbated. Moreover, RES enhanced fertility and protected spermatogenesis by reducing oxidative stress and exerting anti‐apoptotic effects against testicular injury induced by many anticancer drugs 70–73 . In addition, it successfully increases the activity of the antioxidant defense system, prevents LPO, and improves the pathological changes in rats after malathion treatment 74 .…”
Section: Discussionmentioning
confidence: 99%
“…The rats were allocated into 4 groups at random, eight rats per group ( n = 8), assigned as follows: Group (1): Normal control; Group (2): Irradiated (IR) with 6 Gy 24 . Group (3): NAM + IR rats were dosed once daily at 100 mg/kg/dose 25 for 5 days before irradiation; Group (4): RSV + IR, rats were dosed once daily at 10 mg/kg/dose 26 for 5 days before irradiation.…”
Section: Methodsmentioning
confidence: 99%